Glycan masking in immunogen design: computational and experimental methods - Araiza, Gustavo; Morel, Josuel; Tran, Minh H.; Jiang, Shan; Murray, Sean; Miyamoto, Emika; Vogts, Hannah; Brown, Kyle L.; Meiler, Jens; Martina, Cristina E. (Frontiers in Immunology, 2026)
Epitope-focused vaccine design aims to improve upon existing immunization strategies by eliciting immune responses against specific epitopes targeted by known therapeutic antibodies. One of the techniques in epitope-focused immunogen design is glycan masking, in which sugars are used to hide epitopes on the protein of interest that are associated with low therapeutic potency. Here, we provide a detailed overview of the computational and experimental techniques associated with glycan masking for immunogen design at a biochemical and biophysical level. We will cover well-established and emerging in silico methods for predicting and engineering glycosylation sites. Additionally, we will discuss expression and validation of glycosylated immunogens in vitro. We hope this review will be a useful overview for scientists interested in performing glycan masking in their field of research.